Solid electrolyte, method for producing the same, and lithium ion battery
Patent Information
- Application Number
- CN202211151387.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-09-21
AI Technical Summary
制备上述复合电极时,同样需要加入导电剂来提高复合电极的电子电导率,操作繁琐
[0056]本发明提供了一种固体电解质的制备方法,固体电解质原料与导电剂共同混合得到分散良好、组分均匀的混合物,热处理过程中固体电解质原料反应生成固体电解质,而导电剂不参与反应,反应后导电剂仍旧均匀分布在生成的固体电解质中,从而提高固体电解质的电子电导率。并且通过调节导电剂的含量,能实现固体电解质电子电导率的精确调控。
Smart Images

Figure CN115548426B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrolyte materials technology, and relates to a solid electrolyte, its preparation method, and a lithium-ion battery. Background Technology
[0002] Solid electrolytes are the core material of all-solid-state batteries. Solid electrolytes often have high ionic conductivity and low electronic conductivity, making them suitable for electrolyte layers that only require ionic conductivity and not electronic conductivity. However, when solid electrolytes are used as electrode materials, they require both ionic and electronic conductivity. When using the aforementioned solid electrolytes to prepare electrodes, no additional conductive agents are needed.
[0003] CN105229841B discloses a sulfide-based solid electrolyte for lithium-ion batteries. The preparation method involves weighing and ball-milling the raw materials, then calcining them in an inert gas atmosphere such as hydrogen sulfide or argon. The sulfide solid electrolyte prepared by this method exhibits high ionic conductivity while being electronically insulating, making it suitable for use as an electrolyte layer but unsuitable as an electrode material.
[0004] CN105406033B discloses a positive electrode mixture, a positive electrode, a solid-state battery, and methods for manufacturing them. This patent uses a method of preparing electrode materials by mixing particulate and fibrous conductive agents into the electrode. To obtain electrode materials with high ionic and electronic conductivity, the preparation of the positive electrode mixture requires first mixing particulate and fibrous conductive agents, then adding positive electrode active material, then adding solid electrolyte, and finally adding binder. The above-mentioned positive electrode preparation method has a long process flow, is cumbersome, and requires the addition of additional conductive agents.
[0005] CN105591105A discloses a high-cycle-performance lithium-ion battery and its preparation method. The method involves preparing a composite positive and negative electrode by coating the surfaces of positive and negative electrode sheets with a solid electrolyte composite solution, and then using this electrode to fabricate a lithium-ion battery. The solid electrolyte composite solution mainly consists of a solid electrolyte, a conductive agent, a film-forming agent, a binder, and a solvent. However, the preparation of this composite electrode also requires the addition of a conductive agent to improve its electronic conductivity, making the process cumbersome.
[0006] Therefore, there is an urgent need for a solid electrolyte that combines high ionic conductivity and high electronic conductivity to prepare electrodes and simplify the process. Summary of the Invention
[0007] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a solid electrolyte, its preparation method and lithium-ion battery, which can improve the electronic conductivity of the solid electrolyte while ensuring high ionic conductivity, is suitable for electrode preparation, can omit conductive agents and simplify the process.
[0008] To achieve this objective, the present invention adopts the following technical solution:
[0009] In a first aspect, the present invention provides a method for preparing a solid electrolyte, the method comprising:
[0010] A mixture is obtained by mixing a solid electrolyte raw material with a conductive agent, and the mixture is then subjected to heat treatment to obtain a solid electrolyte.
[0011] This invention provides a method for preparing a solid electrolyte. Solid electrolyte raw materials and a conductive agent are mixed together to obtain a well-dispersed and homogeneous mixture. During heat treatment, the solid electrolyte raw materials react to form a solid electrolyte, while the conductive agent does not participate in the reaction. After the reaction, the conductive agent remains uniformly distributed in the resulting solid electrolyte, thereby improving the electronic conductivity of the solid electrolyte. Furthermore, by adjusting the content of the conductive agent, the electronic conductivity of the solid electrolyte can be precisely controlled.
[0012] As a preferred embodiment of the present invention, the conductive agent comprises a carbon material.
[0013] Preferably, the carbon material includes any one or a combination of at least two of zero-dimensional carbon materials, one-dimensional carbon materials, or two-dimensional materials, and is preferably a zero-dimensional carbon material and / or a one-dimensional carbon material.
[0014] Preferably, the zero-dimensional carbon material comprises conductive carbon black and / or conductive graphite, more preferably Ketjen black and / or Super-P.
[0015] Preferably, the one-dimensional carbon material includes any one or a combination of at least two of carbon nanotubes, carbon nanorods, or vapor-grown carbon fibers.
[0016] Preferably, the two-dimensional material includes graphene and / or graphene oxide.
[0017] In this invention, zero-dimensional carbon materials and / or one-dimensional carbon materials are preferred, as they can better improve the electronic conductivity of the solid electrolyte while maintaining high ionic conductivity. Using two-dimensional carbon materials may obstruct the ion transport channels of the solid electrolyte, resulting in a lower ionic conductivity in the prepared solid electrolyte.
[0018] In this invention, the zero-dimensional carbon material preferably comprises Ketjen Black and / or Super-P. This is because Ketjen Black and Super-P have smaller primary particle sizes than other conductive carbon materials, and at the same mass content, smaller particle sizes are more likely to form an excellent conductive network. Furthermore, Ketjen Black and Super-P are dot-like materials, making them easier to disperse uniformly in the raw materials compared to materials such as carbon nanotubes, carbon fibers, and graphene.
[0019] In a preferred embodiment of the present invention, the solid electrolyte is a sulfide electrolyte. Based on a total weight of 100 parts of the solid electrolyte raw material, the weight percentages of each component in the solid electrolyte raw material are as follows:
[0020]
[0021] It should be noted that if the weight percentage of a certain component in the solid electrolyte raw material is 0, it means that the solid electrolyte raw material does not contain this component; if the weight percentage of a certain component in the solid electrolyte raw material is not 0, it means that the solid electrolyte raw material includes this component.
[0022] In this invention, the weight parts of lithium sulfide can be 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85 or 90 parts, but are not limited to the listed values. Other unlisted values within this range are also applicable.
[0023] The weight parts of phosphorus pentasulfide may be 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38 or 40 parts, but are not limited to the listed values. Other unlisted values within this range are also applicable.
[0024] The weight parts of the lithium halide can be 0, 5, 10, 15, 20, 25, 30, 35, 40 or 45, but are not limited to the listed values. Other unlisted values within this range are also applicable.
[0025] The germanium sulfide may be in parts by weight of 0, 2, 4, 6, 8, 10, 12, 14, 16, 18 or 20, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0026] The weight parts of the silicon sulfide may be 0, 2, 4, 6, 8, 10, 12, 14, 16, 18 or 20 parts, but are not limited to the listed values. Other unlisted values within this range are also applicable.
[0027] The weight parts of tin sulfide may be 0, 2, 4, 6, 8, 10, 12, 14, 16, 18 or 20 parts, but are not limited to the listed values. Other unlisted values within this range are also applicable.
[0028] The solvent may be 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60 parts by weight, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0029] As a preferred embodiment of the present invention, the lithium halide includes any one or a combination of at least two of lithium fluoride, lithium chloride, lithium bromide or lithium iodide.
[0030] The present invention does not limit the type of solvent, as long as the solvent does not react with the solid electrolyte raw material. Exemplarily, it includes, but is not limited to, any one or at least a combination of two of heptane, toluene, xylene, ethanol, tetrahydrofuran or tetramethylethylenediamine.
[0031] In this invention, if the solid electrolyte raw material includes a solvent, the mixture obtained after mixing the solid electrolyte raw material and the conductive agent is first dried and then heat-treated. This invention does not specifically limit the drying temperature and time; for example, the drying temperature is 120°C and the drying time is 40 minutes.
[0032] As a preferred embodiment of the present invention, the molar ratio of lithium sulfide, phosphorus pentasulfide and lithium halide is (3-7):1:(0-3.5), wherein the range of lithium sulfide is 3-7, for example, 3, 4, 5, 6 or 7; the range of lithium halide is 0-3.5, for example, 0, 1, 2, 3 or 3.5, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0033] Preferably, the mass ratio of the conductive agent to the total mass of the solid electrolyte raw material and the conductive agent is (0.5-10):100, more preferably (6-10):100. For example, it can be 0.5:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0034] In this invention, there is a preferred range for the ratio of the mass of the conductive agent to the total mass of the solid electrolyte raw materials and the conductive agent. If the mass ratio is less than 0.5:100, the synthesized electrolyte will have insufficient electronic conductivity because the low content of conductive agent is insufficient to construct a good conductive network in the electrolyte. Conversely, if the mass ratio is greater than 10:100, the synthesized electrolyte will have reduced ionic conductivity, affecting the overall performance of the electrolyte. This is because the high content of conductive agent occupies too much electrolyte volume, affecting the ionic conductivity of the electrolyte.
[0035] As a preferred technical solution of the present invention, the mixing method includes at least one of ball milling, roller milling, sand milling or homogenization treatment.
[0036] The present invention does not specifically limit the equipment used in the combination, such as a high-energy ball mill, roller mill, sand mill or homogenizer.
[0037] Preferably, the rotational speed of the ball mill is 100 to 400 rpm, for example, it can be 100 rpm, 120 rpm, 140 rpm, 160 rpm, 180 rpm, 200 rpm, 220 rpm, 240 rpm, 260 rpm, 280 rpm, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm or 400 rpm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0038] Preferably, the ball milling time is 0.5 to 24 hours, for example, it can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, or 24 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0039] Preferably, the temperature of the heat treatment is 160 to 600°C, for example, it can be 160°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0040] Preferably, the heat treatment time is 2 to 24 hours, for example, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0041] Preferably, the heating rate of the heat treatment is 2 to 12 °C / min, for example, it can be 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 8.5 °C / min, 9 °C / min, 9.5 °C / min, 10 °C / min, 10.5 °C / min, 11 °C / min, 11.5 °C / min or 12 °C / min, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0042] As a preferred technical solution of the present invention, the preparation method includes the following steps:
[0043] (1) Lithium sulfide, phosphorus pentasulfide, lithium halide, germanium sulfide, silicon sulfide, tin sulfide and conductive agent are ball-milled and mixed. The ball milling speed is 100-400 rpm and the ball milling time is 0.5-24 h. After mixing, a mixture is obtained, wherein the mass ratio of conductive agent to mixture is (0.5-10):100.
[0044] (2) The mixture in step (1) is heat-treated at 160-600℃ for 2-24 hours and then cooled to obtain a solid electrolyte.
[0045] In a second aspect, the present invention provides a solid electrolyte, which is prepared by the preparation method described in the first aspect, wherein a conductive agent is distributed internally in the solid electrolyte.
[0046] Preferably, the conductive agent is uniformly distributed within the solid electrolyte.
[0047] Thirdly, the present invention provides a lithium-ion battery, wherein the positive electrode compound and / or negative electrode compound of the lithium-ion battery includes the solid electrolyte described in the second aspect. For example, only the positive electrode compound may include the solid electrolyte described in the second aspect, only the negative electrode compound may include the solid electrolyte described in the second aspect, or both the positive electrode compound and the negative electrode compound may include the solid electrolyte described in the second aspect.
[0048] Preferably, the positive electrode mixture and / or negative electrode mixture does not contain a conductive agent. For example, only the positive electrode mixture may not contain a conductive agent, only the negative electrode mixture may not contain a conductive agent, or neither the positive electrode mixture nor the negative electrode mixture may contain a conductive agent.
[0049] Preferably, the positive electrode mixture comprises a solid electrolyte and a positive electrode active material in a mass ratio of (0.1 to 1):1, for example, it can be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0050] Preferably, the negative electrode mixture comprises a solid electrolyte and a negative electrode active material in a mass ratio of (0.1 to 1):1, for example, it can be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0051] The present invention does not specifically limit the type of positive electrode active material, including but not limited to any one or a combination of at least two of lithium cobalt oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide or lithium manganese oxide;
[0052] The present invention does not specifically limit the type of negative electrode active material, including but not limited to any one or a combination of at least two of graphite, silicon carbide or lithium titanate.
[0053] As a preferred technical solution of the present invention, the preparation method of the positive electrode mixture of the lithium-ion battery includes: mixing solid electrolyte and positive electrode active material for 15 to 60 minutes to obtain the positive electrode mixture, for example, mixing for 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes, but not limited to the listed values, other unlisted values within this range are also applicable.
[0054] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0055] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0056] This invention provides a method for preparing a solid electrolyte. Solid electrolyte raw materials and a conductive agent are mixed together to obtain a well-dispersed and homogeneous mixture. During heat treatment, the solid electrolyte raw materials react to form a solid electrolyte, while the conductive agent does not participate in the reaction. After the reaction, the conductive agent remains uniformly distributed in the resulting solid electrolyte, thereby improving the electronic conductivity of the solid electrolyte. Furthermore, by adjusting the content of the conductive agent, the electronic conductivity of the solid electrolyte can be precisely controlled. Attached Figure Description
[0057] Figure 1 This is a schematic diagram of the preparation process of a sulfide solid electrolyte according to a specific embodiment of the present invention.
[0058] Figure 2 This is a schematic diagram of the preparation process of a sulfide solid electrolyte provided in another specific embodiment of the present invention.
[0059] Figure 3 The volume resistivity diagrams of the sulfide electrolytes provided in Examples 1-1 to 1-9, Comparative Examples 1, 2-1 to 2-9, 3-1 to 3-9, and 4-1 to 4-9 of the present invention are shown.
[0060] Figure 4 Volume resistivity diagrams of the positive electrode mixtures provided in Application Examples 1-3 and Comparative Examples 1-3 of the present invention.
[0061] Figure 5 Capacity diagrams of lithium cobalt oxide in the cathode mixtures provided in Application Examples 1-3 and Comparative Examples 1-3 of this invention. Detailed Implementation
[0062] The technical solution of the present invention will be further illustrated below through specific embodiments.
[0063] In one specific embodiment, the present invention provides a method for preparing a sulfide solid electrolyte, such as... Figure 1 The preparation process is illustrated in the schematic diagram. The preparation method includes the following steps:
[0064] A mixture is prepared by mixing sulfide electrolyte raw materials, conductive agent and solvent. The mixture is dried to evaporate the solvent and then calcined to obtain sulfide electrolyte.
[0065] In yet another specific embodiment, the present invention provides a method for preparing a sulfide solid electrolyte, such as... Figure 2 The preparation process is illustrated in the schematic diagram. The preparation method includes the following steps:
[0066] The sulfide electrolyte raw material is mixed with a conductive agent to obtain a mixture, and the mixture is calcined to obtain the sulfide electrolyte.
[0067] Example 1-1
[0068] This embodiment provides a method for preparing a sulfide solid electrolyte, the preparation method is as follows:
[0069] (1) Weigh a total of 4.95g of lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride (LiCl) powders in an argon glove box with a molar ratio of 5:1:2, and 0.05g of conductive agent (the proportion of conductive agent in the solid mixture is 1wt%, and the conductive agent is EC600JD). Pour the weighed total of 5g of powder into a 125ml ball mill jar, add 100g of zirconia beads (φ=5mm), and finally add 10g of dehydrated heptane (moisture content ≤20ppm). After completely sealing the ball mill jar, remove it from the argon glove box.
[0070] (2) The removed ball mill jar was installed into a planetary ball mill and ball-milled at 350 rpm for 15 hours. The ball-milled jar was then returned to the argon glove box, and the zirconia beads were separated to obtain the ball-milled sample. The ball-milled sample was then dried on a 120℃ plate for 40 minutes.
[0071] (3) After the solvent is evaporated, the sample is placed in a tantalum crucible, the lid is closed, and the sample is placed in a muffle furnace in a glove box and heated to 550°C at a heating rate of 10°C / min and held for 4 hours to obtain a sulfide solid electrolyte.
[0072] Examples 1-2 to 1-9
[0073] This embodiment provides a method for preparing a sulfide solid electrolyte: the difference from Example 1-1 is that in step (1), the proportion of the conductive agent in the solid mixture is adjusted to 2-9 wt%, and Examples 1-2 to 1-9 correspond to 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt% and 9 wt% respectively. Other operating steps and process parameters are exactly the same as in Example 1-1.
[0074] Example 2
[0075] This embodiment provides a method for preparing a sulfide solid electrolyte, the preparation method is as follows:
[0076] (1) Weigh a total of 4.5g of lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride (LiCl) powders in an argon glove box with a molar ratio of 5:1:2, and 0.5g of conductive agent (the proportion of conductive agent in the solid mixture is 10wt%, and the conductive agent is EC600JD). Pour the weighed total of 5g of powder into a 125ml ball mill jar, add 100g of zirconia beads (φ=5mm), and finally add 10g of dehydrated heptane (moisture content ≤20ppm). After completely sealing the ball mill jar, remove it from the argon glove box.
[0077] (2) The removed ball mill jar was installed into a planetary ball mill and ball-milled at 250 rpm for 5 hours. After ball milling, the jar was returned to the argon glove box, and the zirconia beads were separated to obtain the ball-milled sample. The ball-milled sample was then dried on a 120℃ plate for 40 minutes.
[0078] (3) After the solvent is evaporated, the sample is placed in a tantalum crucible, the lid is closed, and the sample is placed in a muffle furnace in a glove box and heated to 400°C at a heating rate of 9°C / min and kept at that temperature for 10 hours to obtain a sulfide solid electrolyte.
[0079] Example 3
[0080] This embodiment provides a method for preparing a sulfide solid electrolyte, the preparation method is as follows:
[0081] (1) Weigh a total of 4.975 g of lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride (LiCl) powders in an argon glove box with a molar ratio of 5:1:2, and 0.025 g of conductive agent (the proportion of conductive agent in the solid mixture is 0.5 wt%, and the conductive agent is EC600JD). Pour the weighed total of 5 g of powder into a 125 ml ball mill jar, add 100 g of zirconia beads (φ=5 mm), and finally add 10 g of dehydrated heptane (moisture content ≤20 ppm). After completely sealing the ball mill jar, remove it from the argon glove box.
[0082] (2) The removed ball mill jar was installed into a planetary ball mill and ball-milled at 150 rpm for 20 hours. After ball milling, the jar was returned to the argon glove box, and the zirconia beads were separated to obtain the ball-milled sample. The ball-milled sample was then dried on a plate at 120°C for 40 minutes.
[0083] (3) After the solvent is evaporated, the sample is placed in a tantalum crucible, the lid is closed, and the sample is placed in a muffle furnace in a glove box and heated to 200°C at a heating rate of 8°C / min and kept at that temperature for 20 hours to obtain a sulfide solid electrolyte.
[0084] Example 4
[0085] This embodiment provides a method for preparing a sulfide solid electrolyte: the difference from Examples 1-6 is that in step (1), the conductive agent is changed to carbon nanotubes, and the other operation steps and process parameters are exactly the same as those in Examples 1-6.
[0086] Example 5
[0087] This embodiment provides a method for preparing a sulfide solid electrolyte: the difference from Examples 1-6 is that in step (1), the conductive agent is changed to graphene, and the other operation steps and process parameters are exactly the same as those in Examples 1-6.
[0088] Example 6
[0089] This embodiment provides a method for preparing a sulfide solid electrolyte: the difference from Example 1-1 is that the proportion of conductive agent in the solid mixture is adjusted to 0.2 wt%, while other operating steps and process parameters are exactly the same as in Example 1-1.
[0090] Example 7
[0091] This embodiment provides a method for preparing a sulfide solid electrolyte: the difference from Example 1-1 is that the proportion of conductive agent in the solid mixture is adjusted to 12 wt%, while the other operating steps and process parameters are exactly the same as in Example 1-1.
[0092] Example 8
[0093] This embodiment provides a method for preparing a sulfide solid electrolyte, the preparation method is as follows:
[0094] (1) Weigh a total of 4.7g of lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium iodide (LiI) powders in an argon glove box with a molar ratio of 3:1:0.3, and 0.3g of conductive agent (the proportion of conductive agent in the solid mixture is 6wt%, and the conductive agent is EC600JD). Pour the weighed total of 5g of powder into a 125ml ball mill jar, add 100g of zirconia beads (φ=5mm), and finally add 10g of dehydrated heptane (moisture content ≤20ppm). After completely sealing the ball mill jar, remove it from the argon glove box.
[0095] (2) The removed ball mill jar was installed into a planetary ball mill and ball-milled at 350 rpm for 15 hours. The ball-milled jar was then returned to the argon glove box, and the zirconia beads were separated to obtain the ball-milled sample. The ball-milled sample was then dried on a 120℃ plate for 40 minutes.
[0096] (3) After the solvent is evaporated, the sample is placed in a tantalum crucible, the lid is closed, and the sample is placed in a muffle furnace in a glove box and heated to 200°C at a heating rate of 9°C / min and kept at that temperature for 4 hours to obtain a sulfide solid electrolyte.
[0097] Example 9
[0098] This embodiment provides a method for preparing a sulfide solid electrolyte, the preparation method is as follows:
[0099] (1) Weigh a total of 4.7g of lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), lithium chloride (LiCl), and lithium bromide (LiBr) powders in an argon glove box with a molar ratio of 1.9:0.5:1:0.6, and 0.3g of conductive agent (the proportion of conductive agent in the solid mixture is 6wt%, and the conductive agent is EC600JD). Pour the weighed total of 5g of powder into a 125ml ball mill jar, add 100g of zirconia beads (φ=5mm), and finally add 10g of dehydrated heptane (moisture content ≤20ppm). After completely sealing the ball mill jar, remove it from the argon glove box.
[0100] (2) The removed ball mill jar was installed into a planetary ball mill and ball-milled at 350 rpm for 15 hours. The ball-milled jar was then returned to the argon glove box, and the zirconia beads were separated to obtain the ball-milled sample. The ball-milled sample was then dried on a 120℃ plate for 40 minutes.
[0101] (3) After the solvent is evaporated, the sample is placed in a tantalum crucible, the lid is closed, and the sample is placed in a muffle furnace in a glove box and heated to 440°C at a heating rate of 9°C / min and held for 4 hours to obtain a sulfide solid electrolyte.
[0102] Comparative Example 1
[0103] This comparative example provides a method for preparing a sulfide solid electrolyte: the difference from Example 1-1 is that no conductive agent is added, and only 5g of lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride (LiCl) powder are weighed. Other operating steps and process parameters are exactly the same as in Example 1-1.
[0104] Comparative Example 2-1
[0105] This comparative example provides a method for preparing a sulfide solid electrolyte, the preparation method is as follows:
[0106] (1) Weigh 4.95g of lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride (LiCl) powder in an argon glove box with a molar ratio of 5:1:2. Pour the weighed 4.95g of powder into a 125ml ball mill jar, add 100g of zirconium oxide beads (φ=5mm), and finally add 10g of dehydrated heptane (moisture content ≤20ppm). After completely sealing the ball mill jar, remove it from the argon glove box.
[0107] (2) The removed ball mill jar was installed into a planetary ball mill and ball-milled at 350 rpm for 15 hours. The ball-milled jar was then returned to the argon glove box, and the zirconia beads were separated to obtain the ball-milled sample. The ball-milled sample was then dried on a 120℃ plate for 40 minutes.
[0108] (3) Place the sample after the solvent has been evaporated into a tantalum crucible, close the lid, and place it in a muffle furnace in a glove box. Heat it to 550°C at a heating rate of 10°C / min and keep it at that temperature for 4 hours to obtain the original sulfide electrolyte.
[0109] (4) Weigh 0.05g of conductive agent (EC600JD) and 4.95g of original sulfide electrolyte, totaling 5g (the proportion of conductive agent in the solid mixture is 1wt%). Mix the conductive agent (EC600JD) and original sulfide electrolyte in a mortar for 15min in a glove box to obtain the final sulfide solid electrolyte.
[0110] Comparative Examples 2-2 to 2-9
[0111] This comparative example provides a method for preparing a sulfide solid electrolyte: the difference from Comparative Example 2-1 is that in step (4), the proportion of the conductive agent in the solid mixture is adjusted to 2 to 9 wt%, and Comparative Examples 2-2 to 2-9 correspond to 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, and 9 wt%, respectively. Other operating steps and process parameters are exactly the same as those in Comparative Example 2-1.
[0112] Comparative Example 3-1
[0113] This comparative example provides a method for preparing a sulfide solid electrolyte: the difference from Comparative Example 2-1 is that in step (4), the mixing time is adjusted to 30 min, and the other operation steps and process parameters are exactly the same as those in Comparative Example 2-1.
[0114] Comparative Examples 3-2 to 3-9
[0115] This comparative example provides a method for preparing a sulfide solid electrolyte: the difference from Comparative Example 3-1 is that in step (4), the proportion of the conductive agent in the solid mixture is adjusted to 2 to 9 wt%, and Comparative Examples 3-2 to 3-9 correspond to 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, and 9 wt%, respectively. Other operating steps and process parameters are exactly the same as those in Comparative Example 3-1.
[0116] Comparative Example 4-1
[0117] This comparative example provides a method for preparing a sulfide solid electrolyte: the difference from Comparative Example 2-1 is that in step (4), the mixing time is adjusted to 60 min, and the other operation steps and process parameters are exactly the same as those in Comparative Example 2-1.
[0118] Comparative Examples 4-2 to 4-9
[0119] This comparative example provides a method for preparing a sulfide solid electrolyte: the difference from Comparative Example 4-1 is that in step (4), the proportion of the conductive agent in the solid mixture is adjusted to 2 to 9 wt%, while Comparative Examples 4-2 to 4-9 correspond to 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, and 9 wt%, respectively. Other operating steps and process parameters are exactly the same as those in Comparative Example 4-1.
[0120] The sulfide solid electrolytes obtained in Examples 1-1 to 1-9, Examples 2 to 7, Comparative Example 1, Comparative Examples 2-1 to 2-9, Comparative Examples 3-1 to 3-9, and Comparative Examples 4-1 to 4-9 were pressed into a mass with an area of approximately 1 cm² under a pressure of 350 MPa. 2A circular disc with a thickness of approximately 1 mm was used. The volume resistivity of each electrolyte was tested, recorded, and calculated using an electrochemical workstation. The test results are shown in Tables 1 and 2. The volume resistivity of the sulfide solid electrolytes of Examples 1-1 to 1-9, Comparative Examples 1, 2-1 to 2-9, 3-1 to 3-9, and 4-1 to 4-9 is summarized in... Figure 3 middle, Figure 3 The horizontal axis represents the content of conductive agent in the sulfide electrolyte. The four broken lines correspond from left to right to Examples 1-1 to 1-9, Comparative Examples 4-1 to 4-9, Comparative Examples 3-1 to 3-9, and Comparative Examples 2-1 to 2-9, respectively. The point with a horizontal axis of 0 corresponds to Comparative Example 1.
[0121] Table 1
[0122]
[0123]
[0124] Table 2
[0125]
[0126]
[0127] As can be seen from the results of Examples 1-1 to 1-9, by adjusting the content of the conductive agent, the volume resistivity of the solid electrolyte can be adjusted, thereby achieving precise control of the electronic conductivity of the solid electrolyte.
[0128] The results from Examples 1-6, 4, and 5 show that the type of conductive agent directly affects the ionic conductivity of the solid electrolyte, but has little effect on the electronic conductivity. On the one hand, the solid electrolytes prepared in Examples 1-6, 4, and 5 all exhibited high electronic conductivity; on the other hand, the solid electrolytes prepared using Ketjen black and carbon nanotubes in Examples 1-6 and 4 exhibited high ionic conductivity, while the solid electrolyte prepared using graphene in Example 5 exhibited low ionic conductivity. Solid electrolytes with both high ionic and high electronic conductivity are more suitable for electrode preparation; therefore, zero-dimensional carbon materials and one-dimensional carbon materials are preferred as conductive agents.
[0129] As can be seen from the results of Examples 1-1, 6 and 7, if the content of the conductive agent is too low, it is difficult to form an effective electronic conductive network and the volume resistivity cannot be effectively reduced. If the content of the conductive agent is too high, although a good conductive network can be formed, the reduction in the volume conductivity of the electrolyte is limited. On the contrary, the excessive electrolyte content affects the ionic conductive network of the electrolyte, resulting in a decrease in the ionic conductivity of the electrolyte.
[0130] As can be seen from the results of Examples 1-1 and Comparative Example 1, adding a conductive agent to the solid electrolyte raw material can reduce the volume resistivity of the solid electrolyte, thereby improving the electronic conductivity of the solid electrolyte.
[0131] As can be seen from the results of Examples 1-1 to 1-9 and Comparative Examples 2-1 to 2-9, under the same conductive agent content, compared with the original solid electrolyte and the conductive agent being directly mixed, the solid electrolyte prepared by adding the conductive agent to the solid electrolyte raw material has a lower volume resistivity and better conductivity.
[0132] The results of Examples 1-1 to 1-9, Comparative Examples 2-1 to 2-9, Comparative Examples 3-1 to 3-9 and Comparative Examples 4-1 to 4-9 show that, under the same conductive agent content, even if the mixing time of the original solid electrolyte and the conductive agent is extended to 60 min, its volume resistivity is still higher than that of the solid electrolyte prepared by adding the conductive agent to the electrolyte raw material.
[0133] Application Example 1
[0134] This application example provides a method for preparing a positive electrode mixture, the preparation method being as follows:
[0135] In an argon glove box with water and oxygen levels ≤1ppm, weigh 3g of lithium cobalt oxide and 1g of sulfide solid electrolyte, which is prepared by the method provided in Examples 1-6. Mix the weighed lithium cobalt oxide and sulfide solid electrolyte in a mortar for 15min in the glove box to obtain the positive electrode mixture.
[0136] Application Example 2
[0137] This application example provides a method for preparing a positive electrode mixture. The difference between this method and Application Example 1 is that the mortar mixing time is adjusted to 30 minutes, while the other operating steps and process parameters are exactly the same as in Application Example 1.
[0138] Application Example 3
[0139] This application example provides a method for preparing a positive electrode mixture. The difference between this method and Application Example 1 is that the mortar mixing time is adjusted to 60 min, while the other operating steps and process parameters are exactly the same as in Application Example 1.
[0140] Application Example 4
[0141] This application example provides a method for preparing a positive electrode mixture, the preparation method being as follows:
[0142] In an argon glove box with water and oxygen levels ≤1ppm, weigh 3g of lithium cobalt oxide and 1.5g of sulfide solid electrolyte, which is prepared by the method provided in Examples 1-4. Mix the weighed lithium cobalt oxide and sulfide solid electrolyte in a mortar for 60min in the glove box to obtain the positive electrode mixture.
[0143] Application Comparison Example 1
[0144] This application comparative example provides a method for preparing a positive electrode mixture, the preparation method being as follows:
[0145] In an argon glove box with water and oxygen levels ≤1 PPM, weigh 2.955 g of lithium cobalt oxide, 0.985 g of sulfide solid electrolyte, and 0.06 g of conductive agent (EC600JD). The sulfide solid electrolyte is prepared by the method provided in Comparative Example 1. Mix the weighed lithium cobalt oxide, sulfide solid electrolyte, and conductive agent in a mortar for 15 min in the glove box to obtain the positive electrode mixture.
[0146] Application Comparison Example 2
[0147] This application comparative example provides a method for preparing a positive electrode mixture. The difference between this method and application comparative example 1 is that the mortar mixing time is adjusted to 30 min, while the other operating steps and process parameters are exactly the same as those in application comparative example 1.
[0148] Application Comparison Example 3
[0149] This application comparative example provides a method for preparing a positive electrode mixture. The difference between this method and application comparative example 1 is that the mortar mixing time is adjusted to 60 min, while the other operating steps and process parameters are exactly the same as those in application comparative example 1.
[0150] The volume resistivity of the positive electrode mixtures prepared for Application Examples 1-4 and Comparative Examples 1-3 was tested, and the results are shown in Table 3. The volume resistivity of the positive electrode mixtures for Application Examples 1-3 and Comparative Examples 1-3 is summarized in Table 3. Figure 4 , Figure 4 The two broken lines in the middle correspond to the application examples 1-3 and application examples 1-3 from top to bottom.
[0151] Table 3
[0152]
[0153] The volume resistivity results from Application Examples 1-3 and Comparative Examples 1-3 show that, under the same conductive agent content, the volume resistivity of the positive electrode mixture prepared using the sulfide electrolytes of Examples 1-6 is lower than that prepared using the sulfide electrolyte of Comparative Example 1. Even with a mixing time as long as 60 minutes in the Comparative Example, the final volume resistivity of the obtained positive electrode mixture is still higher than that of the Examples. The volume resistivity of the positive electrode mixture reflects the mixing uniformity to a certain extent; the lower the volume resistivity, the higher the mixing uniformity. The positive electrode mixture prepared using the sulfide electrolytes of Examples 1-6 was basically uniformly mixed after 15 minutes of mixing, while the positive electrode mixture prepared using the sulfide electrolyte of Comparative Example 1, even after 60 minutes of mixing, still did not achieve the same mixing effect as the mixture prepared using the sulfide electrolyte of Examples 1-6 after 15 minutes of mixing. This indicates that using the solid electrolyte of the present invention to prepare the positive electrode mixture can significantly shorten the mixing time and improve efficiency.
[0154] The positive electrode mixtures prepared in Application Examples 1-3 and Application Control Examples 1-3 were used to assemble batteries. The negative electrode mixture for the battery was prepared as follows: 3g of artificial graphite and 2g of sulfide solid electrolyte were weighed in an argon glove box with water and oxygen values ≤1ppm. The sulfide solid electrolyte was prepared by the method provided in Examples 1-6. The weighed artificial graphite and sulfide solid electrolyte were mixed in a mortar and pestle in the glove box for 15min to obtain the negative electrode mixture.
[0155] The above-prepared positive electrode and negative electrode mixtures are assembled into a battery, and the specific steps are as follows:
[0156] (1) Weigh 60 mg of the electrolyte prepared in Comparative Example 1 and pour it into a container with a cross-section of approximately 1 cm. 2 Inside a cylindrical battery insulating sleeve (inner diameter 11.30mm, outer diameter 50mm), insert the upper electrode (φ11.28mm stainless steel) until it touches the powder. Then, rotate both the upper and lower electrodes (φ11.28mm stainless steel) 360° relative to the insulating sleeve to even out the poured electrolyte powder. Finally, apply the powder at a rate of 1 ton / cm². 2 A solid electrolyte layer was prepared by pressing under pressure for 60 seconds.
[0157] (2) Weigh 25 mg of the prepared positive electrode mixture and pour it onto the upper electrode side surface of the solid electrolyte layer. Then, insert the upper electrode until it touches the powder. Next, rotate the upper electrode 360° relative to the battery insulating sleeve at a speed of 3 ton / cm. 2 The pressure was pressed for 60 seconds to obtain a bi-structured disc composed of a positive electrode agent layer and an electrolyte layer.
[0158] (3) Turn the insulating sleeve 180°, weigh 15mg of negative electrode mixture, pour it onto the lower electrode side surface of the solid electrolyte layer, and put the lower electrode on until the electrode touches the powder. Then, rotate the lower electrode 360° relative to the insulating sleeve at a speed of 3ton / cm. 2 Pressurize for 60 seconds, then release the pressure and apply another 5 tons / cm² pressure. 2 Press down at 10 tons / cm for 60 seconds, then release the pressure and pressurize again. 2 The pressure was pressed for 60 seconds to obtain a three-layer structure disc composed of a positive electrode layer, a solid electrolyte layer and a negative electrode layer.
[0159] (4) An aluminum foil (φ11.28mm) is placed on the surface of the positive electrode compound layer as the positive electrode current collector, and a copper foil (φ11.28mm) is placed on the surface of the negative electrode compound layer as the negative electrode current collector to form an all-solid-state battery.
[0160] (5) The battery, along with the insulating sleeve, is sealed and stored with the upper and lower electrodes in a sealed container.
[0161] For each positive electrode compound, three batteries (battery A, battery B, and battery C) were assembled for parallel testing. All three batteries underwent charge-discharge tests. The specific testing steps are as follows:
[0162] (1) Place the battery obtained above into a pressurized charge-discharge fixture. The fixture applies a pressure of 1 ton / cm to the battery through the upper and lower electrodes. 2 The pressure is used for pressurized charging and discharging;
[0163] (2) The charging and discharging test conditions are as follows: the charging and discharging cutoff voltage is set to 2 to 4.2V, the CC charging and discharging current is 0.15mA, and the charging and discharging data of the first week are recorded.
[0164] The capacity test results are shown in Table 4 and Figure 5 As shown, Figure 5 The two broken lines in the middle correspond to application examples 1-3 and application comparison examples 1-3 from top to bottom.
[0165] Table 4
[0166]
[0167] The capacity results from Application Examples 1-3 and Control Examples 1-3 show that, under the same conductive agent content, the capacity of the batteries assembled with the positive electrode mixtures of Application Examples 1-3 is higher than that of the batteries assembled with the positive electrode mixtures of Control Examples 1-3. The average capacity of batteries A, B, and C is the actual capacity of lithium cobalt oxide. The results indicate that using the solid electrolyte of the present invention to prepare the positive electrode mixture can improve the capacity of the positive electrode active material, which is beneficial to battery operation.
[0168] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a solid electrolyte, characterized in that, The preparation method includes: A mixture is obtained by mixing a solid electrolyte raw material with a conductive agent, and the mixture is then subjected to heat treatment to obtain a solid electrolyte. The conductive agent includes zero-dimensional carbon materials and / or one-dimensional carbon materials; The mass ratio of the conductive agent to the total mass of the solid electrolyte raw material and the conductive agent is (0.5~10):100; The solid electrolyte contains a conductive agent distributed inside; The conductive agent is uniformly distributed inside the solid electrolyte.
2. The preparation method according to claim 1, characterized in that, The zero-dimensional carbon material includes conductive carbon black and / or conductive graphite.
3. The preparation method according to claim 1, characterized in that, The zero-dimensional carbon material includes Ketjen Black and / or Super-P.
4. The preparation method according to claim 1, characterized in that, The one-dimensional carbon material includes any one or a combination of at least two of carbon nanotubes, carbon nanorods, or vapor-grown carbon fibers.
5. The preparation method according to claim 1, characterized in that, The solid electrolyte is a sulfide electrolyte. Based on a total weight of 100 parts, the weight percentages of each component in the solid electrolyte raw material are as follows: Lithium sulfide 30-90 parts; 10-40 parts of phosphorus pentasulfide; Lithium halide 0-45 parts; Germanium sulfide 0-20 parts; 0-20 parts of silicon sulfide; Tin sulfide 0-20 parts; Solvent: 0-60 parts.
6. The preparation method according to claim 5, characterized in that, The lithium halide includes any one or a combination of at least two of lithium fluoride, lithium chloride, lithium bromide, or lithium iodide.
7. The preparation method according to claim 5, characterized in that, The molar ratio of lithium sulfide, phosphorus pentasulfide and lithium halide is (3~7):1:(0~3.5).
8. The preparation method according to claim 1, characterized in that, The mixing method includes ball milling.
9. The preparation method according to claim 8, characterized in that, The ball mill rotates at a speed of 100~400 rpm.
10. The preparation method according to claim 8, characterized in that, The ball milling time is 0.5 to 24 hours.
11. The preparation method according to claim 1, characterized in that, The heat treatment temperature is 160~600℃.
12. The preparation method according to claim 1, characterized in that, The heat treatment time is 2~24 hours.
13. The preparation method according to any one of claims 1-12, characterized in that, The heating rate of the heat treatment is 2~12℃ / min.
14. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: (1) Lithium sulfide, phosphorus pentasulfide, lithium halide, germanium sulfide, silicon sulfide, tin sulfide and conductive agent are ball-milled and mixed. The ball milling speed is 100~400 rpm and the ball milling time is 0.5~24 h. After mixing, a mixture is obtained, wherein the mass ratio of conductive agent to mixture is (0.5~10):
100. (2) The mixture in step (1) is heat-treated at 160~600℃ for 2~24h and then cooled to obtain a solid electrolyte.
15. A solid electrolyte, characterized in that, The solid electrolyte is prepared by the preparation method according to any one of claims 1-14, and the solid electrolyte contains a conductive agent distributed inside. The conductive agent is uniformly distributed inside the solid electrolyte.
16. A lithium-ion battery, characterized in that, The positive electrode and / or negative electrode additives of the lithium-ion battery include the solid electrolyte as described in claim 15.
17. The lithium-ion battery according to claim 16, characterized in that, The positive electrode mixture and / or negative electrode mixture do not contain conductive agents.
18. The lithium-ion battery according to claim 16, characterized in that, The positive electrode mixture comprises a solid electrolyte and a positive electrode active material in a mass ratio of (0.1~1):
1.
19. The lithium-ion battery according to claim 16, characterized in that, The negative electrode mixture comprises a solid electrolyte and a negative electrode active material in a mass ratio of (0.1~1):
1.
20. The lithium-ion battery according to claim 16, characterized in that, The preparation method of the positive electrode agent of the lithium-ion battery includes: The solid electrolyte and the positive electrode active material are mixed for 15-60 minutes to obtain the positive electrode mixture.
Citation Information
Patent Citations
Sulfide-based solid electrolytes for lithium-ion batteries
CN105229841B
Positive electrode compound, positive electrode, solid-state battery and their manufacturing methods
CN105406033B
Preparation method for coating surfaces of electrodes with solid electrolyte complex liquid
CN105591105A
Method for manufacturing solid electrolyte, solid electrolyte, active material layer, method for forming active material layer, separator layer, method for forming separator layer, and all-solid-state battery
JP6534078B1